Age-adjusted survival analysis of lymphoma patients diagnosed from extranodal sites - Musa Alzahrani (Wolters Kluwer Medknow Publications, 2021)
Background: Lymphoma is a cancer of the lymphoid system that typically presents in nodal tissues. Involvement of extranodal sites is less common and has been shown to be associated with worst outcomes. The site of the initial diagnosis could give an idea about the accessibility of diagnostic tissue, disease presentation, behavior, and maybe associated with prognostic significance. Methodology: We retrospectively reviewed all adult lymphoma cases diagnosed with lymphoma in our center from 2008 to 2018 and studied the association between extranodal site of biopsy and overall survival (OS). Logrank method was used to calculate P value, and cox proportional hazard was used for age-adjusted survival analysis. Results: A total of 433 patients were included. Median age was 48 years, 183 (42%) were female, and 143 patients (33%) were diagnosed from extranodal sites. The most common site of extranodal involvement was gastrointestinal tract with 69 cases (16%), followed by lung 16 (4%) then central nervous system 11 (2.5%). The most common pathologic diagnosis was diffuse large B-cell lymphoma 182 (42%), followed by classical Hodgkin lymphoma 139 (32%) and then follicular lymphoma 31 (7%). Patients who were diagnosed from a biopsy obtained from extranodal site had a worst OS as compared to patients diagnosed from nodal sites with a significant P value in univariate analysis 0.049 and P = 0.05 after adjusting for age. Conclusion: Patients diagnosed with lymphoma from an extranodal site have a worst OS even after adjusting for age as compared to those diagnosed from nodal sites.